Feasibility and Limitations of High-Voltage Lithium-Iron-Manganese Spinels. Issue 7 (1st July 2022) - Windmüller, Anna; Renzi, Tatiana; Kungl, Hans; Taranenko, Svitlana; Suard, Emmanuelle; Fauth, François; Duttine, Mathieu; Tsai, Chih-Long; Sun, Ruoheng; Durmus, Yasin Emre; Tempel, Hermann; Jakes, Peter; et al.
Abstract : Positive electrodes with high energy densities for Lithium-ion batteries (LIB) almost exclusively rely on toxic and costly transition metals. Iron based high voltage spinels can be feasible alternatives, but the phase stabilities and optimal chemistries for LIB applications are not fully understood yet. In this study, LiFex Mn2-x O4 spinels with x = 0.2 to 0.9 were synthesized by solid-state reaction at 800 °C. High-resolution diffraction methods reveal gradual increasing partial spinel inversion as a function of x and early secondary phase formation. Mössbauer spectroscopy was used to identify the Fe valences, spin states and coordination. The unexpected increasing lattice parameters with Fe substitution for Mn was explained considering the anion-cation average bond lengths determined by Rietveld analysis and Mn 3+ overstoichiometries revealed by cyclic voltammetry. Finally, galvanostatic cycling of Li-Fe-Mn-spinels shows that the capacity fading is correlated to increased cell polarization for higher upper charging cut-off voltage, Fe-content and C-rate. The electrolyte may also contribute significantly to the cycling limitations.